Effect of abiotic stresses and mitigation strategy associated with their tolerance in wheat - Kumar, Sudhir; Mahapatra, Sunita; Chakroborty, Sunanda; Mukherjee, Subhra (Journal of Cereal Research, 2021)
Global warming influences environmental factors which directly and indirectly affects agricultural crop production by exposing to several new biotic and abiotic stresses. The abiotic stresses like heat, drought, moisture, salinity and pre harvest sprouting stresses are most common whose effect became more severe due to climate change. Globally wheat is the most widely cultivated and used crops due to its economic and social values. Its production and productivity are highly vulnerable to these abiotic stresses. The development of wheat varieties tolerant to these abiotic stresses is a very challenging assignment for wheat researchers. The conventional breeding program is being practiced for such objectives but it will not be sufficient to achieve the target production and more advanced research is needed for better understanding the mechanism of these stresses and how plants became more tolerant. The progress made in the understanding of these abiotic stress tolerances is due to advances in three main research areas: physiology, genetic, and breeding research. Identifying morphological traits, physiological and biochemical traits for précised phenotyping and associated genes contributing to particular stress tolerance is very important under mitigation strategy. Previous studies showed that some abiotic stress tolerance is controlled by a polygene and its genetic constitution will help to analyze the gene network(s) controlling stress tolerance. Furthermore, stress mitigation options particularly through the application of plant hormones, several agronomic interventions, genetic and biotechnological management strategy are convenient for improving plant performances under various abiotic stresses are also essential to stabilize the wheat productivity.